2008
DOI: 10.2478/v10032-008-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plant Pruning on the Light Conditions and Vegetative Development of Eggplant (Solanum Melongena L.) in Greenhouse Cultivation

Abstract: The Effect of Plant Pruning on the Light Conditions and Vegetative Development of Eggplant (Solanum MelongenaL.) in Greenhouse CultivationThe aim of the present investigations was to find the relations between pruning methods and chosen parameters of vegetative eggplant development in greenhouse conditions. The plant shape modifies the photosynthetically active radiation (PAR) conditions in the plant profile. Independence between different pruning methods and vegetative plant development particularly leaves ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
2
19
0
4
Order By: Relevance
“…Several manual operations are performed very steadily: removing the axillary shoots and training the main stem keeps the crop in optimal conditions as regards light interception; deleafing consists in removing the oldest leaves, which are no longer photosynthetically active, in order to avoid plant diseases and facilitate harvesting; truss pruning aims at adapting the fruit load to assimilate production, in order to improve fruit grade and quality (Navarrete and Jeannequin, 2000). Although pruning increases costs in tomato production, it improves light penetration inside the plant canopy and increases photosynthesis efficiency and so fruit yield (Ambroszczyk et al, 2008;Mbinga, 1983;Rajewar and Patil, 1979). Since vegetative growth, as a powerful sink, consumes produced assimilates, limitation of vegetative growth enhances assimilate transport to roots or fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Several manual operations are performed very steadily: removing the axillary shoots and training the main stem keeps the crop in optimal conditions as regards light interception; deleafing consists in removing the oldest leaves, which are no longer photosynthetically active, in order to avoid plant diseases and facilitate harvesting; truss pruning aims at adapting the fruit load to assimilate production, in order to improve fruit grade and quality (Navarrete and Jeannequin, 2000). Although pruning increases costs in tomato production, it improves light penetration inside the plant canopy and increases photosynthesis efficiency and so fruit yield (Ambroszczyk et al, 2008;Mbinga, 1983;Rajewar and Patil, 1979). Since vegetative growth, as a powerful sink, consumes produced assimilates, limitation of vegetative growth enhances assimilate transport to roots or fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Energy-saving techniques have been introduced in eggplant production in the greenhouse to reduce its costs and to increase its efficiency. Among modern techniques, the most promising are grafting (Khah 2005), introduction of bumblebees as pollinators (Abak et al 2000), use of growth regulators (Pessarakli and Dris 2003), use of parthenocarpic eggplant cultivars (Acciarri et al 2002), optimization of growth conditions in relation to phase of plant development (Kurklu et al 1998), and plant pruning (Ambroszczyk et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In studies on eggplant, species of the same family, Ambroszczyk et al (2008) observed that the stem pruning of the eggplant did not show significant effect on the relative index of chlorophyll.…”
Section: Resultsmentioning
confidence: 95%
“…In studies carried out by Marcelis (1996), the leaf area of pepper and tomato was not influenced by pruning of fruits or leaves, but it can be changed by the increase of the sunlight interception in the canopy, due to the change in plant density. Ambroszczyk et al (2008), in studies, on eggplants, grown using different systems of pruning (one and two stems), report higher leaf area in plants grown with one stem, during vegetative phase. However, during fruiting no difference was noticed between the treatments.…”
Section: Resultsmentioning
confidence: 95%